The Acute Effects of 2 Different Intensities of Resistance Exercise on Autonomic Function in Heart Failure Patients: A Randomized Controlled Trial - Marzieh Saeidi; Roya Ravanbod; Mohammad Hossein Pourgharib Shahi; Hosein Navid; Babak Goosheh; Abdolvahab Baradaran; Giti Torkaman (Anatolian Journal of Cardiology, 2023)
Background: Although a wide spectrum of resistance exercise intensities was recommended in the guidelines, none of them investigated the acute effects of different intensities of the resistance exercise on cardiac autonomic function in patients with chronic heart failure. This study aimed to investigate the acute effects of the low and high intensities of the resistance exercise on heart rate variability in chronic heart failure.